A Method of Early Phase Selection of Carrier for Aspergillus Oryzae β‐Galactosidase Immobilization for Galactooligosaccharides Production. Issue 3 (17th May 2018) - Adamíková, Jana; Antošová, Monika; Polakovič, Milan
Abstract : Early phase development of industrial immobilized biocatalysts has to address the selection of the best candidates from dozens of available carriers and binding methods. This work presents a simple selection method for the immobilization of industrial‐grade Aspergillus oryzae β ‐galactosidase suitable for the production of galactooligosaccharides. Immobilization efficiency and yield of a variety of immobilized biocatalysts are evaluated using simple activity measurements and mathematical modeling of intraparticle kinetics and mass transfer. Activated carriers and some ion‐exchange carriers provided highly active biocatalysts and are therefore selected for the investigation of GOS production in the batch reactor. Biocatalysts exhibited significant differences in the yield of galactooligosaccharides and productivity of GOS formation. Based on these process performance criteria, cost considerations are made that allow further selection of the best biocatalyst for future process optimization. The presented method of biocatalyst selection can be useful for other industrial enzymes applications. Abstract : Galactooligosaccharides are non‐digestible prebiotics that have generated interest in food industry as an ingredient of functional food. In this study, the authors deal with the immobilization of the enzyme β ‐galactosidase on a variety of carriers and characterize the process performance and cost aspects of selected biocatalysts. This work can be utilized in the optimization of the large‐scale production of galactooligosaccharides.